173k views
0 votes
How do I solve? (10y+9)-(4y-8)=​

2 Answers

5 votes

Answer:

(10y + 9) - (4y - 8) = 6y + 17

Explanation:


(10y+9)-(4y-8)\\\\=10y+9-4y-(-8)\\\\=10y+9-4y+8\qquad\text{combine like terms}\\\\=(10y-4y)+(9+8)\\\\=6y+17

User Alex Nguyen
by
6.3k points
3 votes

Answer:

(6y+17)

Explanation:

1. Subtract 4y from 10y to get 6y

2. 9 is positive and 8 is negative but to subtract a negative is basically adding so you would add 9 to 8

3. You final equation would be (6y+17)

4. (10y+9)-(4y-8)= (6y+17)

User Hugo Sama
by
6.1k points